Family Influence on School Performance - Buzaitytė-Kašalynienė, Jolita (Acta Paedagogica Vilnensia, 2004)
Scientific problem refers to the lack of investigations that provide answers to the question what family factors influence student's school performance. The purpose of the research is to reveal peculiarities of family factors and student's school performance in comprehensive schools. The aim of this article is to reveal the influence of family factors on school performance. The research was carried out applying the following research methods: analysis of scientific literature, survey research, and statistical data analysis. It was developed students survey questionnaire with 236 multiple-choice items. These items address students' self-assessments of their beliefs about their social environment – neighbourhoods, schools, friends, and families - and about their own psychological health and school performance. The research is based on the answers of 1071 students (577 boys and 494 girls) of eighth grade. The paper reports only part of the research results. Data analysis reveals that higher family integration, parent social support, home academic climate, parent education monitoring are associated with better school performance: attendance, grades, and behaviour, so these family factors can be defined as protective factors. And low safety at home, high family psychosocial and material problems are associated with worse or lower school performance, so these family factors can be defined as risks. Risk can be defined as any influence that increases the probability of onset, digression to a more serious state, the maintenance of a problem condition. There are different types of risks, including individual risk traits, environmental risks, and stressful life events. Protective factors are generally strengths that are present in individuals or in the environments and they help reduce the impact of the risks. The balance of risk and protective factors students experience in their social environment influences the level of success they experience at school.
Keywords: school; school performance; family; environment influences; social support